Perspectives on dialogue in the new millennium - Kühnlein, Peter; Rieser, Hannes; Zeevat, Henk, 1952- (Pragmatics & beyond, 2003)
The formal treatment of the semantics and pragmatics of dialogue became possible through a series of breakthroughs in foundational methodology. There is broad consensus on a couple of issues, like the fact that some variety of dynamic theory is necessary to capture certain characteristics of dialogue. Other matters still are disputed. This volume contains papers both of foundational and applied orientation. It is the result of one of a series of specialized Workshops on Formal Semantics and Pragmatics of Dialogue that took place in 2001. One can therefore truly say that it mirrors both th.